Long-term histological and mucin alterations in the neobladder mucosa following urinary bladder augmentation or substitution with gastrointestinal segment. Issue 6 (December 2015) - Kispal, Zoltan Farkas; Kardos, Daniel; Jilling, Tamas; Kereskai, Laszlo; Isaacs, Marla; Balogh, Daniel L.; Pinter, Andrew B.; Till, Holger; Vajda, Peter
Summary: Introduction: Bladder augmentation is widely used to treat otherwise unmanageable urinary incontinence. However, it is associated with a large number of complications, of which tumor formation is the most severe. Mucin proteins and MUC genes are linked, among others, to malignancies of the urinary bladder and the gastrointestinal system. Objective: To investigate histological alterations as well as changes in expression of MUC1 and MUC2 genes and proteins following different types of urinary bladder augmentation or substitution performed in children and adolescents. Patients and methods: Between 1988 and 2013, 91 patients underwent urinary bladder augmentation or substitution at the study institute. Patients were included on whom cystoplasty had been performed 4 years previously or earlier, and could have been followed-up prospectively. Thus, 54 patients were involved in the study. In eight patients gastrocystoplasty was performed, in 17 patients ileocystoplasty, and in 22 patients colocystoplasty. Seven patients underwent bladder substitution using a colonic-segment. Biopsies were taken via cystoscopy from the native bladder, from the gastrointestinal segment used for augmentation, and from the anastomotic line between these two. One part of the samples was fixed in formaldehyde for routine histological processing. The other part of the biopsies was embedded into OCT medium, then cryosectioned and fluorescently double-immunostained for MUC1 and MUC2 proteins. Samples from the microscopically dysplastic lesions and from the 15-year-old or older biopsies were processed by laser capture microdissection, and then real-time PCR was done. Data were statistically analyzed by ANOVA and ordinary least squares regression tests. Results: One adenocarcinoma was found in a female patient, 11 years after colocystoplasty. There were no significant changes in the level of MUC1 and MUC2 proteins and gene expression in the urothelium and in the gastrointestinal segment used for augmentation following ileocystoplasty and gastrocystoplasty. Significant increase in MUC1 and decrease in MUC2 protein levels were detected following colocystoplasty in the large bowel segment used for augmentation, both with qualitative and quantitative methods ( p  < 0.05) (Figure). The uroepithelium showed no significant change. RT-PCR revealed progressive increase in MUC1 gene expression and decrease in MUC2 gene expression after colocystoplasty in the course of time. It also showed highly increased MUC1 gene expression and decreased MUC2 gene expression in the samples of patients. Conclusions: Alterations in gene expression of MUC1 and MUC2 might serve as promising markers for early detection of histological changes after colocystoplasty. Figure Changes in MUC1 (green) and MUC2 (red) protein levels 4, 11, and 21 years after colocystoplasty. (For interpretation of the references to colour in this figure legend, the reader is referred to the web version of this article.)